Assessment of temperament and its effect on weaning performance for Aubrac and Charolais weaned calves - Szentléleki, Andrea; Domokos, Zoltán; Blottura, Claudio; Alberti, Massimiliano; Tőzsér, János (Acta Agraria Debreceniensis, 2009)
The purposes of the present study are to compare the temperament of calves of different breed and sex at weaning, to analyse the effect of temperament on weaning performance, and todefine the correlations  between the previous traits. In the experiment carried out in Gelej in 2006 the behaviour of 61 Aubrac and 25 Charolais calves (39 heifer and 47 bull calves) wasassessed at weaning. The weight (WW) and the age of animals were detected, in addition temperament (TEMP) of them was scored. The weaning age (AU: 190±16.96 days, CH: 176±14.94days; P